Predicting grey squirrel expansion in North Italy: a spatially explicit modelling approach - LURZ, P. W. W; RUSHTON, S. P; WAUTERS, L. A; BERTOLINO, S; CURRADO, I; MAZZOGLIO, P; SHIRLEY, F (Landscape ecology, 2001)
There is growing concern about the spread of the North American grey squirrel (Sciurus carolinensis) in northern Italy which were introduced into Piedmont in 1948. They have since spread across the Po-plain covering an area of approximately 450 km2 and continue to expand their range. In parallel to what has been observed in Britain and Ireland, grey squirrels replace the native red squirrel (S. vulgaris) and damage poplar (Populus) plantations through bark-stripping. Spatially explicit population dynamics models have been successfully used to predict the spread of grey squirrels in East Anglia, England. We extended a previous approach employing a sensitivity analysis where life history and other demographic inputs are generated using Latin Hypercube Sampling from the known ranges of each input parameter, and applied it to Italy using field data collected in Piedmont. The analysis indicated that reproductive output was the most important factor determining total population size present in Piedmont. The structure and composition of woodland habitats around the introduction site suggested that initial grey squirrel expansion would have been slow and subject to emigration rates from the available habitat blocks.A comparison of the 1996 survey results with model predictions indicated that a mean litter size of three young gave the best fit with the observed distribution and we use this to predict future grey squirrel spread. We also present a ‘worst case’ scenario in which grey squirrels experience improved reproductive success due to the availability of high quality habitats beyond the Po plain. In both cases they could disperse along existing continuous woodland corridors into France between 2039–2048. The case of the grey squirrel highlights the problems of implementing conservation conventions and the resulting conflicts between wildlife management, public perception and local political support and the narrow time frame that is available to control alien species effectively before it is too late. If allowed to spread, grey squirrels have the potential of becoming a European forest pest species and are likely to replace the native red squirrel in large parts of its range.